2016
DOI: 10.3389/fmicb.2016.01539
|View full text |Cite
|
Sign up to set email alerts
|

Production Strategies and Applications of Microbial Single Cell Oils

Abstract: Polyunsaturated fatty acids (PUFAs) of the ω-3 and ω-6 class (e.g., α-linolenic acid, linoleic acid) are essential for maintaining biofunctions in mammalians like humans. Due to the fact that humans cannot synthesize these essential fatty acids, they must be taken up from different food sources. Classical sources for these fatty acids are porcine liver and fish oil. However, microbial lipids or single cell oils, produced by oleaginous microorganisms such as algae, fungi and bacteria, are a promising source as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
160
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(161 citation statements)
references
References 218 publications
(300 reference statements)
0
160
0
1
Order By: Relevance
“…This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/). lipids, since they grow fast and accumulate substantial amounts of lipids (Ochsenreither et al, 2016;Sitepu et al, 2014). Numerous microalgae are also recognised lipid producers since their productivity exceeds other photosynthetic organisms, without competing for arable land (Sibi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/). lipids, since they grow fast and accumulate substantial amounts of lipids (Ochsenreither et al, 2016;Sitepu et al, 2014). Numerous microalgae are also recognised lipid producers since their productivity exceeds other photosynthetic organisms, without competing for arable land (Sibi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although oleaginous microorganisms are attractive sources of biodiesel feedstocks, the production of microbial lipids needs to be economically competitive with petroleum-based fuels (Sitepu et al, 2014). As certain cultivation conditions, mainly nutrient limitation in combination with carbon excess, trigger lipid accumulation in many oleaginous microorganisms (Ochsenreither et al, 2016), the carbon source in the growth medium is of central importance. The choice of carbon source plays a very important role in process economics and it was demonstrated that the use of glucose during lipid production from Rhodosporidium toruloides accounts for the 80% of the total raw material cost (Koutinas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that fish sources of PUFA may contain heavy metals as contaminants . Alternatively, PUFA may be produced by microorganisms, both yeasts and bacteria, using bioprocess technology, which does not add environmental hazards and does not compete with food production . Agro‐industrial residues can be applied as substrates for bioprocess systems, further contributing to reduce production costs and environmental problems, as it is discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…1 Alternatively, PUFA may be produced by microorganisms, both yeasts and bacteria, using bioprocess technology, which does not add environmental hazards and does not compete with food production. 6 Agro-industrial residues can be applied as substrates for bioprocess systems, further contributing to reduce production costs and environmental problems, as it is discussed below. The oil produced by oleaginous microorganisms, known as single cell oil (SCO), can be used in several industrial applications from food industries to biofuels, and their composition depend on the strain used and the cultivation conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation